Gender and Family Stereotypes in a Photograph: Research Using the Eye-Tracking Method - Labischová Denisa; Kalitová Kristina (De Gruyter, 2024)
The article presents the results of a 2022 study involving students training to be civic studies teachers. Three research goals were set: to determine which gender and family stereotypes burden the interpretation of a photograph; to identify qualitative differences in the perception, analysis, and interpretation of the photograph depending on the form of the questions asked; and to gain respondents' feedback on the test. The test used a computer and was based on a family photograph and a series of questions. Three methods of data collection and analysis were used (audio recording analysis, eye-tracking, interview). The study found that future teachers are substantially influenced by gender stereotypes in Czech society. It also confirmed the importance of didactic structuring when analysing iconographic material. The findings show the importance of gender-sensitive education and the development of didactic skills for interpreting visual texts as part of undergraduate training for future civic studies teachers.